Correction: β-Cyclodextrin modified graphitic carbon nitride for the removal of pollutants from aqueous solution: experimental and theoretical calculation study. Issue 18 (29th April 2019) - Zou, Yidong; Wang, Xiangxue; Ai, Yuejie; Liu, Yunhai; Ji, Yongfei; Wang, Hongqing; Hayat, Tasawar; Alsaedi, Ahmed; Hu, Wenping; Wang, Xiangke
Abstract : Correction for 'β-Cyclodextrin modified graphitic carbon nitride for the removal of pollutants from aqueous solution: experimental and theoretical calculation study' by Yidong Zou et al., J. Mater. Chem. A, 2016, 4, 14170–14179.